2013
DOI: 10.1108/17410391311289613
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health records

Abstract: Purpose -The purpose of this paper is to understand one aspect of electronic health record adoption by studying the impact of policy interventions on the adoption among hospitals, physicians and patients, using a system dynamics simulation model. Design/methodology/approach -A system dynamics simulation model of the existing distribution network was built. Policy experiments were conducted to compare the performance of each. Findings -Using data from the Greater Capital Region, Northern New York State, the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…43,44 High-quality training may facilitate use of advanced EHR capabilities. [45][46][47][48][49][50][51] Associations between SDH awareness and awareness of other advanced EHR capabilities reveal that lack of awareness is not unique to SDH functions and training to increase awareness could therefore target a broad set of these high-value functions.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 High-quality training may facilitate use of advanced EHR capabilities. [45][46][47][48][49][50][51] Associations between SDH awareness and awareness of other advanced EHR capabilities reveal that lack of awareness is not unique to SDH functions and training to increase awareness could therefore target a broad set of these high-value functions.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency service [111] Supply-demand equation that delivers frontline policing services Air transportation [112] policies and strategies for air transportation (e.g., policies for reducing emissions of commercial aviation Local public policy [113] local public policy process Public sector unit [114] mortality rate of public sector units Concession pricing model [115] determining a rational concession price for highway projects based on pro forma financial statements Highway sustainability [116] highway sustainability based on individual policies with a crucial impact on the success of policymaking Academic performance [117] factors that affect academic performance of migrant student residing in poor migrant neighborhoods Maritime Sustainability [118] integrated sustainability assessment process Information in health care [119] emergent market behaviour enabling evaluation of different public health policies Climate change [120] electricity industry at the same time as addressing climate change issues Participatory urban [121] urban sensing for improving municipality's availability of environmental information at comparable cost level Wireless local area [122] effect of subsidization, revenue sharing, and alliance strategies Airport competitiveness [123] airport investment and city R&D inputs, which support decision-makers on airport competitiveness Electronic health records [124] combination of measures can promote the adoption of electronic health records by different stakeholders…”
Section: Topics and Goods Models And Issues Dealtmentioning
confidence: 99%
“…Otto and Nevo (2013) suggested that, along with concern for safety, there are other mitigating factors such as political and economic issues slowing the progress of EHR adoption. Physicians' perceptions and resistance to migrating to EHRs, cited by Otto and Nevo were a loss of control, provider attitude, financial negatives, and continuity of care as an obstacle to adoption.…”
Section: Barriers To Ehr Adoptionmentioning
confidence: 99%